2013
DOI: 10.12996/gmj.2013.24
|View full text |Cite
|
Sign up to set email alerts
|

The Long-term Effect of Uretral Dilatation Therapy Combined with Steroid After Internal Urethrotomy

Abstract: Objective: To present the long-term results of hydrophilic dilatation catheter or steroid-coated hydrophilic dilatation catheter usage in the management of primary urethral stricture. Methods: Forty-one male patients with a diagnosis of primary urethral stricture shorter than 1.5 cm and no comorbities were included in this study. After application of internal uretrotomy, these patients were randomized into two groups. A steroid-coated (triamcinolone acetonide (1%) 18F hydrophilic dilatation catheter was applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…All seven included trials were identified through the literature search [ 18 19 20 21 22 23 24 ]. All trials were randomised and included the administration of steroids (triamcinolone) via a coated catheter or submucosal injection.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…All seven included trials were identified through the literature search [ 18 19 20 21 22 23 24 ]. All trials were randomised and included the administration of steroids (triamcinolone) via a coated catheter or submucosal injection.…”
Section: Resultsmentioning
confidence: 99%
“…All seven included studies [ 18 19 20 21 22 23 24 ] were assessed for a range of risk of bias domains including random sequence generation, allocation concealment, blinding of participants and personnel, blinding of outcome assessments, incomplete outcome data, selective reporting and other bias’. A vast majority of domains across all included trials were assessed to be of unclear risk of bias due to insufficient information.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations